2015
DOI: 10.7863/ultra.34.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultrasound Implementation on Physical Examination Learning and Teaching During the First Year of Medical Education

Abstract: Ultrasound implementation into a physical diagnosis curriculum for year 1 medical students is feasible and may improve their overall traditional physical examination skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 44 publications
1
97
0
7
Order By: Relevance
“…This is a set of ultrasound examinations that parallel the 'Stanford 25', a set of core physical examinations that institutions recommend should be familiar to students. Dinh et al [46] found that students that had ultrasound incorporated into their physical examination curriculum obtained greater OSCE scores than a cohort of students that took the exams prior to the introduction of ultrasound, in the same medical school. The educational interventions found here range from those that teach students to scan a wide range of anatomy [47,48] or regional anatomy [49] to more focused exams of the vascular [50][51][52], abdominal [53][54][55], head and neck [56], cardiac [57,58] and respiratory [59] systems.…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
“…This is a set of ultrasound examinations that parallel the 'Stanford 25', a set of core physical examinations that institutions recommend should be familiar to students. Dinh et al [46] found that students that had ultrasound incorporated into their physical examination curriculum obtained greater OSCE scores than a cohort of students that took the exams prior to the introduction of ultrasound, in the same medical school. The educational interventions found here range from those that teach students to scan a wide range of anatomy [47,48] or regional anatomy [49] to more focused exams of the vascular [50][51][52], abdominal [53][54][55], head and neck [56], cardiac [57,58] and respiratory [59] systems.…”
Section: Learning Category-incorporation Of Ultrasound Into Teaching mentioning
confidence: 99%
“…While some medical schools have achieved this through introduction of ultrasound into early physical examination and anatomy courses [11][12]19 , one-time seminars 14,15 and 4 th year electives 16 , these approaches may not work across all medical school curricula. Previous success had been reported with implementation of a theme-based format when similar short blocks of time were used for educational purposes with point-of-care ultrasound (POCUS).…”
Section: Discussionmentioning
confidence: 99%
“…Early introduction of ultrasound as a tool to augment physical examination teaching has been shown to not only be well received by students, but also appears to improve overall physical examination skills. [10][11][12] Early introduction of ultrasound in medical school has led to success in both increased objectively graded Objective Standardized Clinical Examination (OSCE) testing and ultrasound skill level. 11,13 Alternatively, short elective courses, seminars and symposia have also shown great success in engaging learners and improving ultrasound knowledge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this trend can be observed worldwide, from rural areas in developing countries to top-quality medical schools and tertiary referral hospitals [8-17]. …”
Section: Introductionmentioning
confidence: 99%